1992
DOI: 10.1902/jop.1992.63.5.477
|View full text |Cite
|
Sign up to set email alerts
|

The Connective Tissue and Partial Thickness Double Pedicle Graft: A Predictable Method of Obtaining Root Coverage

Abstract: Obtaining predictable root coverage has been a goal of periodontal therapy for sometime. The purpose of this study is to present a technique for obtaining root coverage. This study reports the results of 20 patients (30 defects) treated with a connective tissue and partial thickness double pedicle graft. Root coverage of 100% was obtained in 24 of 30 defects, or 80% of the time. In all the treated defects the root coverage obtained was to within 0.5 mm of the cemento-enamel junction. The mean percent root cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
226
3
35

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(272 citation statements)
references
References 3 publications
8
226
3
35
Order By: Relevance
“…[12][13][14][15][16][17][18] Also, the root coverage gained with SCTG procedures was reported to be stable over the long-term. 14 Therefore, SCTG procedures have commonly served as the ''gold standard'' to evaluate the safety and results of new root-coverage techniques.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Also, the root coverage gained with SCTG procedures was reported to be stable over the long-term. 14 Therefore, SCTG procedures have commonly served as the ''gold standard'' to evaluate the safety and results of new root-coverage techniques.…”
mentioning
confidence: 99%
“…The main goal of this study was to com- The reported root coverage in this study is lower than that from other studies, in a comparative study between CT and ADM grafts used in a bilaminar techniques 16,20,21,[33][34][35][36][37] , but well within the range of reported root coverage. 30 .…”
Section: ⅳ Discussionmentioning
confidence: 98%
“…An SCTG is usually harvested from the palate and placed over the recession and under a mucoperiosteal flap. The SCTG technique offers excellent esthetic result, as well as a very predictable percentage of root coverage, when properly indicated 1,7,8,13,14,20) . In many cases, more than one procedure is necessary to treat gingival recession.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of a laterally positioned flap was employed to increase the amount of attached tissue on Tooth #31 from Tooth #32. Concomitantly, the SCTG was also employed for this objective as previously described in the literature 1,[13][14][15] . The tunnel technique was carried out to ensure the preservation of the interproximal papilla 1) and facilitate fixation of the graft for root coverage.…”
Section: Discussionmentioning
confidence: 99%